“CNN Can Kiss My As$” - Andrea Lorenz; Carolyn Schmitt; Shannon McGregor; Daniel Malmer (Journal of Quantitative Description: Digital Media)
News consumption in the United States is polarized and fragmented, with an abundance of partisan news publications appealing to political identities on both the left and the right. Yet, there is an abundance of hyperpartisan news on the right, the content of which has been shown to be harmful to democracy. This study captures one of the most comprehensive pictures to date of the U.S. Americans who consume far-right media and makes connections between such media use and the state of American democracy. After a lengthy data-cleaning process, we analyzed open-ended survey responses from a nationally representative sample of more than 10,000 U.S. American adults, finding that nearly ten percent self-report at least one far-right news outlet as a primary news source. Furthermore, significantly more U.S. Americans report consuming far-right and moderate-right news outlets than counterparts on the left. We then examined the characteristics of this small but significant group, given the current political climate in the United States, finding that far-right news consumers are overwhelmingly white, male, Republican, Christian, and without a college degree. This study reinforces previous findings that patterns in hyperpartisan media usage demonstrate growing extremism in the U.S., and that it is deeply rooted in identity.